KOMBINASI PUPUK KANDANG KAMBING DAN KALIUM NITRAT (KNO3) TERHADAP PERTUMBUHAN DAN KECEPATAN BERBUNGA JAGUNG MANIS (Zea mays saccharata) - Fitriyah, Nur; Rahmatika, Widyana; melya Contesya, Sherlin (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2024)
Zea mays Saccharata (Sweet corn) is a horticultural commodity that is have high carbohydrates and contains free sugars and starch (Wahditiya, 2016). sweet corn imports increased 42.46% from 517.5 thousand tons in the previous year to 737.2 thousand tons (BPS, 2021 in Amelia and Sugiharto, 2022). This high demand is not matched by availability. Efforts to meet this demand include improving cultivation techniques such as used of superior varieties and ecological management. The combination of organic and anorganic fertilizers can play an important role because it can maintain soil health, productivity and plant fertility. The combination of goat fertilizer and KNO3 is expected to increase vegetative and generative performance. The research method used RAKF. The first factor is the dose of goat manure, K1 = 5 tons/ha, K2 = 10 tons/ha, K3 = 15 tons/ha. The second factor is the application of white KNO3 fertilizer P1 = 50 kg/ha, P2 = 100 kg/ha, P3 = 150 kg/ha. There were 9 treatment combinations and repeated 3 times and 5 samples. The observed parameters include: Plant height, number of leaves, leaf area, and flowering age. Data obtained from the observations of each variable were subjected to the F test with the method of variance (ANOVA). If the treatment combination accepted H1 then the comparison test will be done BNT 5%. The results showed that there was no interaction between the application of goat manure and KNO3 on the growth and yield. The application of KNO3 has a significant effect on the vegetative period of the plant number of leaves, plant height, stem diameter, and early flowering age of the plant.